New combinations in Potentilla for taxa originally validated or treated in Ivesia, Horkelia, and Horkeliella (Rosaceae: Potentilleae) - Mosyakin, Sergei L.; Ertter, Barbara; Shiyan, Natalia M. (Phytotaxa, 2020)
Nineteen new combinations (eight species-rank and 11 variety-rank ones) in Potentilla (Rosaceae, Potentilleae) are proposed for North American taxa that were originally validated or treated in Ivesia, Horkelia, and Horkeliella. These combinations are needed for those researchers and users of botanical nomenclature who prefer to subsume these taxa in Potentilla in its updated monophyletic (holophyletic) circumscription. That circumscription is mainly based on recent molecular phylogenetic results that demonstrated that the three ivesioid genera form a monophyletic lineage (ivesioid clade) that is phylogenetically rooted in the core clade of Potentilla. Nomenclatural comments are provided, and the rationale of those preferring the continued recognition of Ivesia, Horkelia, and Horkeliella is explained.